Calcium signaling in cognition and aging-dependent cognitive decline - Oliveira, Ana; Bading, Hilmar (Biofactors, 2011)
Calcium-dependent signals are key triggers of the molecular mechanisms underlying learning and memory and dysregulation of calcium homeostasis in the aging brain has been proposed to underlie aging-dependent cognitive decline. Mechanisms triggered by calcium in neurons include activity-dependent activation of transcription responsible for the synthesis of molecules underlying the long-term changes of neuronal function. Effectors of calcium signaling with a primordial role in transcription regulation are calcium signal-regulated transcription factors. In this review, we summarize the current knowledge of the contribution of key calcium signal-regulated transcription factors, namely CREB, NFAT, and DREAM, to memory formation. We further describe evidence for dysregulation of the activity of these factors during aging.
Gesehen am 12.10.2022